A review on applications of solar energy for preheating in power plants - Khalid Almutairi; Mohammad Alhuyi Nazari; Mohamed Salem; Mohammad Mehdi Rashidi; Mamdouh El Haj Assad; Sanjeevikumar Padmanaban (Alexandria Engineering Journal, 2022)
One of the main approaches for performance improvement of thermal power plants is employing preheating units. Preheating the air or stream in Brayton or Rankine cycles can significantly improve the overall efficiency output power. Solar energy, as an available renewable energy, is an attractive option to be employed as the source of preheating. In the present article, applications of solar energy for preheating air and steam in thermal power plants are reviewed. According to reviews, enhancement in the performance of the systems is under influence of several factors such as the configuration of reference system, operating condition, applied technology etc. Besides performance enhancement of the power plant, integration of solar preheating system can remarkably reduce the fuel consumption and consequently the emission of carbon dioxide. Furthermore, due to the unavailability of the solar energy in nigh and cloudy hours, applying thermal storage units can enhance the reliability of the system and increase contribution of solar energy in the output of the system.